Diseño y elaboración de material didáctico en kichwa para el aprendizaje de la asignatura de Estudios Sociales del cuarto y séptimo año de educación general básica, en la escuela Liliana Rojas Miranda - Guzman Reinoso, Rocio Margoth (2015)
The teaching material includes the means and resources to facilitate the teaching-learning process, stimulating the function of the senses to obtain readily the content of the lesson plan. We are currently in a time of many changes in the educational system, this makes it vital to implement new teaching strategies that are based on the use and application of properly teaching materials used in the lesson plan established as it reaches constitute the support of the methodology that seeks to raise interest in and desire for student participation. Education is the instrument of transformation of society, contributes to the construction of the country, project life and liberty of its citizens, peoples and nationalities. Recognizes human beings in particular children and adolescents at the center of a process of learning and subjects of rights. The proper and timely interaction with exposure learning resource of knowledge in the classroom, will significantly improve the process of knowledge acquisition in students. The material developed will fill this educational void found in this institution, we can say without fear of contradiction that the study of the Kichwa should be included within the crosscutting issues of education, because only that way you can keep current language mother. As such the development of training material that supports learning in teaching in the area of Social Studies, the fourth and seventh year of general basic education School Canton Liliana Rojas Miranda Cayambe, parish Cangahua is important